Targeting the Oncogenic TBX2 Transcription Factor With Chromomycins - Sahm, Bianca Del B.; Peres, Jade; Rezende-Teixeira, Paula; Santos, Evelyne A.; Branco, Paola C.; Bauermeister, Anelize; Kimani, Serah; Moreira, Eduarda A.; Bisi-Alves, Renata; Bellis, Claire; Mlaza, Mihlali; Jimenez, Paula C.; et al. (Frontiers in Chemistry, 2020)
The TBX2 transcription factor plays critical roles during embryonic development and it is overexpressed in several cancers, where it contributes to key oncogenic processes including the promotion of proliferation and bypass of senescence. Importantly, based on compelling biological evidences, TBX2 has been considered as a potential target for new anticancer therapies. There has therefore been a substantial interest to identify molecules with TBX2-modulatory activity, but no such substance has been found to date. Here, we adopt a targeted approach based on a reverse-affinity procedure to identify the ability of chromomycins A5 (CA5) and A6 (CA6) to interact with TBX2. Briefly, a TBX2-DNA-binding domain recombinant protein was N-terminally linked to a resin, which in turn, was incubated with either CA5 or CA6. After elution, bound material was analysed by UPLC-MS and CA5 was recovered from TBX2-loaded resins. To confirm and quantify the affinity (KD) between the compounds and TBX2, microscale thermophoresis analysis was performed. CA5 and CA6 modified the thermophoretic behaviour of TBX2, with a KD in micromolar range. To begin to understand whether these compounds exerted their anti-cancer activity through binding TBX2, we next analysed their cytotoxicity in TBX2 expressing breast carcinoma, melanoma and rhabdomyosarcoma cells. The results show that CA5 was consistently more potent than CA6 in all tested cell lines with IC50 values in the nM range. Of the cancer cell types tested, the melanoma cells were most sensitive. The knockdown of TBX2 in 501mel melanoma cells increased their sensitivity to CA5 by up to 5 times. Furthermore, inducible expression of TBX2 in 501mel cells genetically engineered to express TBX2 in the presence of doxycycline, were less sensitive to CA5 than the control cells. Together, the data presented in this study suggest that, in addition to its already recognized DNA-binding properties, CA5 may be binding the transcription factor TBX2, and it can contribute to its cytotoxic activity.